Comparative Analysis of Affordable Housing Financing Models : United States and Sub-Saharan Africa - Babra Kyokusiima (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This abstract examines and contrasts affordable housing financing models in the United States and Sub-Saharan Africa, highlighting regulatory, institutional, and market-driven determinants that shape affordability outcomes. In the United States, a mature ecosystem of instruments Low-Income Housing Tax Credits (LIHTC), government-sponsored mortgage insurance programs, tax-exempt housing bonds, public housing authorities, and layered subsidy mechanisms supports supply-side production and preserves long-term affordability through legally enforceable covenants and deep capital markets. In Sub-Saharan Africa, financing remains constrained by shallow mortgage markets, limited formal lending, tenuous land tenure, and heavy reliance on informal savings, microfinance, remittances, donor grants, development finance institutions, and nascent public–private partnership arrangements. This comparative analysis evaluates models across key dimensions: scale and outreach, cost-efficiency, administrative complexity, fiscal sustainability, risk allocation, and inclusion of the lowest-income households. The findings indicate that U.S. instruments have achieved measurable scale and predictability because of secondary markets, tax incentives, and robust institutional capacity, yet they can generate spatial concentration of subsidized stock and entrenched subsidy burdens. Sub-Saharan African approaches display local adaptability and incremental housing pathways that suit informal urban expansion but suffer from high unit financing costs, currency and interest-rate volatility, inadequate risk pooling, and weak legal protections for tenants. Policy implications emphasize hybrid strategies: developing secondary mortgage mechanisms and mortgage-backed instruments where feasible, expanding blended finance and performance-based subsidies, clarifying land tenure and regulatory frameworks, and mobilizing concessional capital to lower unit costs. Transferable lessons include rigorous monitoring frameworks and demand-side targeting, while respecting locally driven incremental finance methods. These recommendations aim to improve affordability, resilience, and equitable access across divergent institutional contexts. Future research should employ comparative longitudinal data, randomized pilots of financing interventions, and stakeholder cost-benefit analyses to identify scalable models that balance fiscal prudence with social equity, enabling policymakers and practitioners to design context-appropriate financing pathways. globally.